Comparison between Slow Components of HR and V˙O2 Kinetics: Functional Significance. Issue 8 (August 2018) - ZUCCARELLI, LUCREZIA; PORCELLI, SIMONE; RASICA, LETIZIA; MARZORATI, MAURO; GRASSI, BRUNO
ABSTRACT: Purpose: Aerobic exercise prescription is often based on a linear relationship between pulmonary oxygen consumption (V˙O2 ) and heart rate (HR). The aim of the present study was to test the hypothesis that during constant work rate (CWR) exercises at different intensities, the slow component of HR kinetics occurs at lower work rate and is more pronounced that the slow component of V˙O2 kinetics. Methods: Seventeen male (age, 27 ± 4 yr) subjects performed on a cycle ergometer an incremental exercise to voluntary exhaustion and several CWR exercises: 1) moderate CWR exercises, below gas exchange threshold (GET); 2) heavy CWR exercise, at 45% of the difference between GET and V˙O2 peak (Δ); 3) severe CWR exercise, at 95% of Δ; 4) "HRCLAMPED " exercise in which work rate was continuously adjusted to maintain a constant HR, slightly higher than that determined at GET. Breath-by-breath V˙O2, HR, and other variables were determined. Results: In moderate CWR exercises, no slow component of V˙O2 kinetics was observed, whereas a slow component with a relative amplitude (with respect to the total response) of 24.8 ± 11.0% was observed for HR kinetics. During heavy CWR exercise, the relative amplitude of the HR slow component was more pronounced than that for V˙O2 (31.6 ± 11.2% and 23.3 ± 9.0%, respectively). During HRCLAMPED, the decrease in work rate (~14%) needed to maintain a constant HR was associated with a decreased V˙O2 (~10%). Conclusions: The HR slow component occurred at a lower work rate and was more pronounced than the V˙O2 slow component. Exercise prescriptions at specific HR values, when carried out for periods longer than a few minutes, could lead to premature fatigue.